Use of a Multiplex Immunoassay Platform to Investigate Multifaceted Antibody Responses in SARS-CoV-2 Vaccinees with and Without Prior Infection - Odo, Troy; Haun, Brien K.; Williams, Caitlin A.; Ball, Aquena; To, Albert; Wong, Teri Ann S.; Ching, Lauren; Nakano, Eileen; Van Ry, Alex; Pessaint, Laurent; Andersen, Hanne; Donini, Oreola; et al. (COVID, 2025)
The emergence of COVID-19 necessitated the rapid development of vaccines. While highly effective at reducing severe disease and death, breakthrough infections remain a problem as the virus continues to mutate. To help address this issue, we show the utility of a multiplex immunoassay in measuring multiple aspects of the antibody response generated by SARS-CoV-2 vaccines. We use a multiplex immunoassay platform to measure spike-specific IgG concentration, avidity, and receptor-binding inhibition. In addition, we correlate results from an ACE-2 receptor-binding inhibition assay with corresponding data from a SARS-CoV-2 microneutralization assay to establish this inhibitory assay as a potential predictor of virus neutralization. We studied these antibody responses in SARS-CoV-2-naïve and -convalescent vaccinees. Our results showed increased IgG concentrations, avidity, and inhibition following vaccination in both groups. We were also able to differentiate the immune response between the two groups using the multiplex immunoassay platform to look at antibody diversity. The receptor-binding inhibition assay has strong correlations with a cell-based pseudovirus neutralization assay as well as with WT SARS-CoV-2 Washington and Delta variant PRNT50 assays. This suggests that the inhibition assay may be able to simultaneously predict virus neutralization of different SARS-CoV-2 variants. Overall, we show that the developed custom multiplex immunoassay with several experimental variations is a powerful tool in assessing multiple aspects of the SARS-CoV-2 antibody response in vaccinated individuals.